Una aproximación integral al diagnóstico y tratamiento del déficit de atención con o sin hiperactividad (2020)
The TDAH is an disorder with genetic predisposition, based on studies that have demonstrated cases in which the parents of hyperactive children presented signs of the disorder during the childhood; it disorder understands a set of biological factors and of characteristics that must be evaluated with thoroughness to be able to emit this diagnostic. Although some classifications try to be ample and deep at the time of identifying the signs corresponding to the disorder, it has been that that make use of them, it is to say to psychiatrists and psychologists mainly, they only identify those characteristics that are common for all the cases leaving of side the individual differences and relational aspects, as they are the etiologics and psycho-social factors.